Determinants of cervical cancer screening uptake among women of childbearing age in Mangochi District Malawi - Mpachika, Felistas Sungeni (2021)
Cervical cancer (CC), a deadly disease, has a high burden and mortality at global and local level. Despite the burden, Malawi registers low uptake of cervical cancer screening (CCS). This study examined the determinants of uptake of cervical cancer screening among women of child bearing age in Mangochi district. A quantitative cross-sectional study was conducted in five health facilities offering visual inspection using acetic acid (VIA). A total of 482 women between the ages of 18-49 were selected using a multi-stage sampling method. Data that were collected through a structured questionnaire were coded and analysed using SPSS version 22. Logistic regression model was used to identify factors associated with CCS. Few respondents (13.1%) had ever been screened for CC. Those between 18-24 years were less likely to undergo CCS compared to those in 25-35 years category (AOR=0.38, 95% CI 0.19-0.77, P = 0.007). Respondents who had not received health education on CC were less likely to undergo CCS than those who had received (AOR=0.20, 95% CI 0.10-0.41, P=0.000). HIV positive respondents were more likely to screen than their HIV negative counterparts (AOR= 2.41, 95% CI 1.22-4.78, P=0.012). Respondents with high-level of knowledge on signs and symptoms of CC were more likely to undergo CCS than those with low-knowledge (AOR=2.91, 95% CI 1.51-5.63, P=0.002). Cervical cancer is preventable and one strategy to prevent it is through timely screening. This study has established that age, religion, ethnicity, residence, HIV status and health education are among the determinants of CCS uptake. We therefore recommend that CCS should be offered to all WCBA in this era of HIV infection, that community based screening services should be encouraged to reach out to more women residing in rural areas, that health education should be offered in all strategic areas in health facilities to give out information to clients accessing other health services and that the integration of antiretroviral therapy (ART) and CCS clinics should be rolled out to most health facilities to offer CCS to HIV positive women.